Investigating the role of relationship satisfaction and paternal psychological distress during pregnancy on offspring health in early life - Korhonen Laura; Nolvi Saara; Peltola Ville; Lukkarinen Minna; Korja Riikka; Karlsson Linnea; Karlsson Hasse (CAMBRIDGE UNIV PRESS, 2025)
Background: The research on the role of father in the foetal programming of health and behaviour has received increasing attention. However, the influences of paternal depressive symptoms and couple relationship satisfaction during pregnancy - potentially mediated via maternal well-being - on the offspring's risk of infections in early life is still seldom assessed.
Aims: The aim was to investigate if paternal psychological distress during pregnancy is associated with elevated risk of recurrent respiratory infections (RRIs) for offspring at 12 months of age, and whether maternal distress mediates the association between paternal distress and offspring RRIs.
Method: The study population was drawn from the nested case-control cohort of the FinnBrain Birth Cohort Study. Children with RRIs (n = 50) were identified by maternal reports at the age of 12 months, whereas mothers did not report RRIs for the comparison group (n = 716). Parental depressive symptoms were measured with the Edinburgh Postnatal Depression Scale and couple relationship satisfaction was measured with the Revised Dyadic Adjustment Scale.
Results: The association between paternal depressive symptoms during pregnancy and offspring RRIs was mediated by maternal prenatal depressive symptoms. Additionally, paternal poorer relationship satisfaction was associated with child RRIs independently of maternal distress.
Conclusions: The results suggest different pathways through which paternal distress during pregnancy may contribute to elevated risk of offspring RRIs, and more research is needed to study their underlying mechanisms. Paternal distress and couple relationship satisfaction during pregnancy should be assessed and screened as a contributor to offspring health.